Fotografia e participação no cotidiano da educação infantil: um olhar para o protagonismo da criança - Mendes, Zilmar Maria Dias (2024)
The need to reflect on how to improve teaching practice and face the challenges posed by children's in-person return to Early Childhood Education spaces after the covid-19 pandemic permeates this research. This is an investigation carried out in a Municipal Early Childhood Education Center in the municipality of São Carlos/SP, which sought to understand how five-year-old children re-established their experiences in the Early Childhood Education school when they returned to activities in person, after the control of the covid-19 pandemic, using photography as a strategy for participation and protagonism. In order to carry out this study, the methodology adopted followed a qualitative approach whose chosen method was Case Study. The theoretical framework of this study is based on Paulo Freire, to discuss Democratic Education; Lev S. Vigotski and the Historical-Cultural Theory, to lead the discussion on children's development through interaction in the social and cultural environment; Júlia Formosinho and João O. Formosinho, to deal with participatory pedagogies in which the children are at the center of the knowledge-building process; Carla Rinaldi in her notes on the importance of listening in the teaching-learning process; Boris Kossoy and Roland Barthes contribute with a theoretical basis on photography, which is an important element in this study. The data used in the research are the images produced by the children and the teacher, as well as the teacher's pedagogical documentation. This study made it possible to reflect on the practice of photographic recording as a listening strategy in early childhood education, as well as a form of expression that allows the teacher to develop a more detailed view of the children's experiences. In the research, the photographic record made by the children was approached as a way of interacting and playing a leading role in the educational process, providing new experiences for the children and the teacher through the exercise of observation and listening and also through the construction of their pedagogical documentation, for which photographic production with and by the children was an essential element. By looking at her own practice and giving visibility to the children's protagonism, the teacher became the protagonist and the children appropriated new conceptions built up in the educational context.